Information processing in patients in vegetative and minimally conscious states. Issue 2 (February 2016) - Real, Ruben G.L.; Veser, Sandra; Erlbeck, Helena; Risetti, Monica; Vogel, Dominik; Müller, Friedemann; Kotchoubey, Boris; Mattia, Donatella; Kübler, Andrea
Highlights: Rates of misdiagnoses in patients with disorders of consciousness (DOC) are high. The auditory P300 was more prevalent in healthy participants than in DOC patients. P300 prevalence did not differentiate between VS and MCS patients. Abstract: Objective: Evaluation of a short two-tone oddball paradigm to discriminate between the vegetative state (VS) and minimal consciousness state (MCS) in a sample of patients with severe disorders of consciousness (DOC). Method: EEG was recorded from 45 DOC patients and 14 healthy participants while listening to an auditory oddball paradigm presented in a passive – just listen – and an active – count the odd tones – condition. In patients, the experiment was repeated after a minimum of one week. Results: Prevalence of the P300 was higher in healthy participants (71%) than in patients, but did not discriminate between VS (T1: ∼10%; T2: ∼11%) and MCS (T1: ∼13%; T2: 25%) patients. Conclusion: Results cast doubt on whether this simple auditory stimulation paradigm, which requires cognitive action from the listener, is sensitive enough to discriminate between patients with DOC. Significance: The sensitivity of the P300 ERP obtained in a short two-tone oddball paradigm presented in a passive and an active condition appears to be too low for routine application in a clinical setting aiming at distinguishing between VS and MCS patients.